Comparison of the expression of the seven ribosomal RNA operons in Escherichia coli. - Condon, C (1992)
We have compared the expression of the seven ribosomal RNA operons (rrn) of Escherichia coli and their responses to a variety of physiological and genetic perturbations. We used a set of rrn promoter fusion constructs in their native chromosomal positions to examine effects of chromosomal location on rrn operon expression and the same set of fusions on lambda lysogens to assay intrinsic promoter strengths independent of chromosome context. In its native chromosomal location, expression of the rrnH operon was significantly lower than expected. This effect was not attributable to weak promoter activity and was dependent on the growth medium. The rrnE operon had reduced promoter activity relative to the other ribosomal operons in minimal medium and thus appears to have abnormal growth rate regulation. The ribosomal RNA operons showed varied responses to amino acid starvation; expression of rrnD was inhibited most. There was only a slight increase in rrn transcription in response to a temperature shift (30 degrees C to 42 degrees C) and the differences between individual operons was very small. The rrnG operon showed a significantly lower response than the other ribosomal RNA operons to a depletion of the rrn transcription activator, Fis, and thus appears to have decreased Fis-mediated transactivation. Finally, the chromosomal fusion strains were used to study the effect on growth rate of inactivating each rrn operon. In fast growth conditions, loss of certain rrn operons caused subtle decreases in growth rate on complex medium.